Digital Inclusive Education in the Educational System - Pirlog, Nicoleta (Didactica Danubiensis, 2024)
This paper addresses the topic of digital inclusive education in today’s continuously transforming educational system. Inclusive education is an ongoing process that involves the schooling of children with special educational needs, adapting schools to their needs, and engaging them in both formal and informal educational activities that ensure their learning and development. Digital inclusion facilitates the teaching, learning, and evaluation processes, providing a playful and dynamic space for students, bringing significant benefits to the education system. Digital inclusion in education is crucial because, beyond approaching interaction means of knowledge, it also motivates the learning process, which requires inventive means and knowledge exchange, ensuring active student participation in school activities. This involves identifying and eliminating barriers that can relate to the way schools are organized, teaching methods, and evaluating student progress. Inclusive education and digital technology are interconnected. Successful transformation of inclusive educational systems must consider successful digital transformation. Although inclusive and digital educational systems have developed separately, their various advances have supported each other. They should be viewed as such, and the connection between them should be further promoted so that all students have equal chances to reach their potential within the educational system.